Cofilin Inhibitor Improves Neurological and Cognitive Functions after Intracerebral Hemorrhage by Suppressing Endoplasmic Reticulum Stress Related-Neuroinflammation - Daniyah A. Almarghalani; Ghaith A. Bahader; Mohammad Ali; L. M. Viranga Tillekeratne; Zahoor A. Shah (MDPI AG, 2024)
Neuroinflammation after intracerebral hemorrhage (ICH) is a crucial factor that determines the extent of the injury. Cofilin is a cytoskeleton-associated protein that drives neuroinflammation and microglia activation. A novel cofilin inhibitor (CI) synthesized and developed in our lab has turned out to be a potential therapeutic agent for targeting cofilin-mediated neuroinflammation in an in vitro model of ICH and traumatic brain injury. The current study aims to examine the therapeutic potential of CI in a mouse collagenase model of ICH and examine the neurobehavioral outcomes and its mechanism of action. Male mice were subjected to intrastriatal collagenase injection to induce ICH, and sham mice received needle insertion. Various concentrations (25, 50, and 100 mg/kg) of CI were administered to different cohorts of the animals as a single intravenous injection 3 h following ICH and intraperitoneally every 12 h for 3 days. The animals were tested for neurobehavioral parameters for up to 7 days and sacrificed to collect brains for hematoma volume measurement, Western blotting, and immunohistochemistry. Blood was collected for cofilin, TNF-α, and IL-1β assessments. The results indicated that 50 mg/kg CI improved neurological outcomes, reversed post-stroke cognitive impairment, accelerated hematoma resolution, mitigated cofilin rods/aggregates, and reduced microglial and astrocyte activation in mice with ICH. Microglia morphological analysis demonstrated that CI restored the homeostasis ramification pattern of microglia in mice treated with CI. CI suppressed endoplasmic reticulum stress-related neuroinflammation by inhibiting inflammasomes and cell death signaling pathways. We also showed that CI prevented synaptic loss by reviving the pre- and post-synaptic markers. Our results unveil a novel therapeutic approach to treating ICH and open a window for using CI in clinical practice.